Revealing the influence of plant-based additives on qualitative indicators of a semi-finished product made from camel meat - Medeubayeva, Zhanar; Tayeva, Aigul; Shambulova, Gulnara; Syzdykova, Laila; Astakhov, Mikhail (Eastern-European Journal of Enterprise Technologies, 2022)
This paper considers the influence exerted on the qualitative indicators of boiled camel sausage by plant-based additives. The study’s results were used to improve the technology and determine the levels of application of plant-derived extracts with antioxidant properties in the production of boiled sausages. The effect of plant extracts with antioxidant properties on oxidative processes in boiled sausages has been investigated. Camel meat contains phosphorus, magnesium, and potassium. This meat has a large content of vitamins A, B1, B2, C, and E. In terms of protein content (15.1 %), camel is inferior to beef; in terms of fat (11.5 %), it is inferior to other types of meat. However, camel meat is rich in vitamins and trace elements. In addition, the composition of camel meat contains phosphorus, 216‒234 mg, which is higher than that of beef. The disadvantage of boiled camel sausages is a short shelf life. Therefore, it was decided to add plant-based supplements with antioxidant properties. In addition, to ensure minimal lipolytic changes and changes in lipid oxidation in meat, the rational concentration of added antioxidants was determined. Using the response surface methodology, a three-level factor plan was constructed for two variables – the concentration of ginger root powder and sea buckthorn powder. The minimum acid number was manifested at 0.018 % of ginger root powder and 0.035 % of sea buckthorn powder. The minimum peroxide number was obtained at 0.028 % of the L-root of ginger and 0.010 % of the powder of sea buckthorn; the minimum TBARS was detected at 0.030 % of the powder of ginger root and 0.050 % of the powder of sea buckthorn. The concentration of ginger root powder with optimal resistance to oxidation and lipolysis is proposed. The shelf life was also determined in comparison with the control